Case Study on Legal Arrangements for Sharia Peer-to-Peer Lending Financing - Dr. Lina Maulidiana, S.H.,M.H; Lenny Nadriana; Rendy Renaldy, S.H., M.Kn.,C.P.Li.,C.P.Arb.,C.P.M.,C.P.C.; Loso Judijanto; Rika Santina, S.H., M.H (Faculty of Law, Universitas Pekalongan, 2025)
The fintech business of peer-to-peer lending has experienced a period of considerable growth in recent years. However, it is still the subject of debate and controversy from the perspective of Sharia law. This article aims to analyze Sharia law on fintech peer-to-peer lending businesses, with a particular focus on usury and gharar banking. The methodology employed in this study is descriptive and analytical in nature. This entailed the collection of data from a range of sources, including literature, legal documents, and expert opinions. The findings indicate that the peer-to-peer lending fintech business can be classified as usury and gharar due to the implementation of several practices by the platform, including high interest rates and a lack of transparency regarding the associated risks. From the perspective of Sharia law, usury and gharar are prohibited, as they contravene the principles of justice and balance. Consequently, fintech peer-to-peer lending businesses must adhere to the tenets of Shariah law, such as abstaining from exorbitant interest rates and ensuring transparency regarding risks. In conclusion, fintech peer-to-peer lending businesses must be meticulously analyzed from the perspective of Shariah law to ensure their halalness in Islam. It is also imperative for the government and regulators to prioritize Shariah law aspects in regulating fintech peer-to-peer lending businesses